2021
DOI: 10.3349/ymj.2021.62.4.279
|View full text |Cite
|
Sign up to set email alerts
|

Serological Biomarkers and Indices for the Current Activity and Prognosis of ANCA-Associated Vasculitis: Experience in a Single Centre in Korea

Abstract: Small vessel vasculitis is composed of two types of vasculitis based on immune-complex deposits, immune-complex vasculitis and antineutrophil cytoplasmic antibody-associated vasculitis (AAV) according to the 2012 Chapel Hill Consensus Conferences Nomenclature of Vasculitis. In general, the current disease-states are assessed in three ways in real clinical practice such as activity, damage and functional status. Birmingham vasculitis activity score (BVAS, version 3) and five-factor score were calculated for ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 71 publications
0
8
0
Order By: Relevance
“…This system includes nine sub-systems and the weighted score for new-onset/worsening or persistence of every symptom is different. Therefore, this system is considered to be the most reliable tool for evaluating AAV activity (14). We further found that the BVAS disease activity score of AAV patients was positively correlated with CRP and NLR, and patients with high CAR and high NLR had higher all-cause mortality rates.…”
Section: Discussionmentioning
confidence: 71%
“…This system includes nine sub-systems and the weighted score for new-onset/worsening or persistence of every symptom is different. Therefore, this system is considered to be the most reliable tool for evaluating AAV activity (14). We further found that the BVAS disease activity score of AAV patients was positively correlated with CRP and NLR, and patients with high CAR and high NLR had higher all-cause mortality rates.…”
Section: Discussionmentioning
confidence: 71%
“…The Severance Hospital ANCA-associated VasculitidEs (SHAVE) cohort was a prospective cohort that consisted of patients with AAV (MPA, GPA, and EGPA). Patients were subjected to clinical and laboratory data assessment and had their blood obtained during routine patient care [ 12 ]. After obtaining patient blood, sera were separated immediately from the whole blood by centrifugation and stored in a deep freezer at -70°C before usage.…”
Section: Methodsmentioning
confidence: 99%
“…The SHAVE cohort is an observational cohort comprising patients classified as having AAV according to the 2007 European Medicine Agency and the 2012 Chapel Hill Consensus Conference definitions 2 , 32 . Among patients included in the SHAVE cohort, clinical data and blood samples of patients with AAV were collected after obtaining consent 33 , 34 . For patients enrolled in this study, written informed consent was obtained from all subjects.…”
Section: Methodsmentioning
confidence: 99%